Penerapan Literasi Digital dalam Membangun Kemampuan Berpikir Kritis Siswa di Sekolah Dasar - Warastuti, Wahyu; Prayitno, Harun Joko; Rahmawati, Laili Etika (Jayapangus Press, 2025)
This study is motivated by the importance of digital literacy in developing students' critical thinking skills in the digital era. With the rapid development of information technology, students' ability to access, analyze, and evaluate information has become a vital skill. The aim of this research is to describe the application of digital literacy in building students' critical thinking skills at SD Negeri 01 Matesih, Karanganyar. The method used is qualitative research with a phenomenological design, involving observation, interviews, and documentation. Data validity is ensured through source triangulation, method triangulation, and member checking with participants. The research findings show that digital literacy is applied through the Problem-Based Learning (PBL) approach, supported by various digital learning applications such as Merdeka Mengajar (PMM), reading corners with QR codes, Canva, Wordwall, and Quizizz. The implementation of PBL provides students with opportunities to actively search for information, analyze content, and verify the accuracy of the information they obtain. This digital-based learning successfully enhances students' critical thinking skills, as the digital media used encourages them to think analytically and reflectively. Additionally, the school's digital literacy programs, such as the barcode reading corners and digital reading corners, provide students with broader access to information that can enrich their knowledge. In conclusion, digital literacy has proven to be an effective tool for enhancing students' critical thinking skills at SD Negeri 01 Matesih.